Massive Open Online Course (MOOC) service quality assessment: Issues and instruments / Safwana Nur Widad, Safri Zurinawati Mohi and Mohd Hafiz Hanafiah - Safri, Safwana Nur Widad; Hanafiah, Mohd Hafiz (Universiti Teknologi MARA, Selangor, 2020)
This paper seeks to explore the issue influencing MOOC platform adoption and usage and reviews the existing literature on measuring users’ perceptions about quality in the online platform. It is a concern about how MOOC platform service quality affects the quality of e-learning process. This paper proposes that a proper MOOC service quality assessment would portray the success of the delivery and design of the platform, especially by understanding the platform’s limitation and users' preferences.